2019
DOI: 10.1016/j.sjbs.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using plant derived 4-N-methyl benzoic acid and evaluation of antimicrobial, antioxidant and antitumor activity

Abstract: The present study is to investigate the antitumor, antioxidant and antibacterial potential of silver nanoparticles (Ag NPs) synthesized from a phenolic derivative 4-N-methyl benzoic acid, isolated from a medicinal plant ( Memecylon umbellatum Burm F ). The Bio-inspired nanoparticles (NPs) were analyzed by using UV–vis spectroscopy, FTIR, HRTEM, Zeta potential and XRD techniques. The UV–vis spectroscopy study at the band of 430 nm confirmed the nanoparticles formation. HRTEM report showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 52 publications
6
28
0
7
Order By: Relevance
“…Thus, for silver the crystallite size was 69(23) Å, and for manganese was 11.953230 Å. Our results are consistent with previous findings [1,25,30,31,[46][47][48]. However, additional peaks were observed, and they could be associated to Ag2O at 2θ values of 27°, 32°, and 44° (PDF card no.…”
Section: Xrd Analysissupporting
confidence: 91%
“…Thus, for silver the crystallite size was 69(23) Å, and for manganese was 11.953230 Å. Our results are consistent with previous findings [1,25,30,31,[46][47][48]. However, additional peaks were observed, and they could be associated to Ag2O at 2θ values of 27°, 32°, and 44° (PDF card no.…”
Section: Xrd Analysissupporting
confidence: 91%
“…Our results are agreed with the previous studies that AgNPs synthesized by using Artemisia haussknechtii leaf aqueous extract showed significant metal-chelating activity (68.93 % ± 2.37) [61]. Silver nanoparticles (AgNPs) synthesized from 4-Nmethyl benzoic acid, which is a phenolic derivative isolated from Memecylon umbellatum Burm F., showed the metal-chelating potential ranging from 21.9% to 82.49% [60]. Liu et al [62] reported that after the boiling procedure, chelating activities of ferrous ions by garlic aqueous extracts increased about 54.7% do not agree with our results.…”
Section: Dpph Radical Scavenging Assaysupporting
confidence: 92%
“…Both the extract and its AgNPs showed 50% scavenging activity at 250 µg/mL [59]. AgNPs synthesized by a green method using 4-N-methyl benzoic acid, which is a phenolic derivative isolated from Memecylon umbellatum Burm F., had the potential scavenge DPPH radical effect (81.57%) [60]. Table 2 results showed that garlic extract (Gaqu) possessed low metal-chelating activity (11.59%) compared to GAgNPs.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…Also, plants produce more various nanoparticles, either in shape or in size. [1][2][3][4][5][6] The nanoparticles have broad-spectrum applications in health care, cosmetics, biomedical food and feed, drug/ gene delivery, environmental studies, mechanics, optics, light limiters, nonlinear optical and photoelectron chemical applications, and that rely on the different synthesis processes. In UV-visibleregions, the versatile semiconductor behavior, their momentous optical transparency and luminescent properties and their applications in solar cells, ceramics, and catalysts, cosmetics, gas sensors, and lighting arrestors.…”
Section: Introductionmentioning
confidence: 99%